Learning Al-Quran and Arabic at the Orphanage: (Community-Based Research) - Muhammad Sapii Harahap; Benny Munardi; Zulham Effendi; Daryanto Setiawan; Fian Triadi; Dasa Syawal Syahputra; Junaidi Junaidi (ASSUNNAH PRESS, 2022)
The Muhammadiyah Lhokseumawe Orphanage in South Hagu Village is one of the orphanages that helps the Lhokseumawe community by giving more comprehensive attention to the education of children who have not had the opportunity to receive a proper education, namely helping to provide guidance and educational opportunities for children. Foster child. On the other hand, children's orphanages also often experience a lack of attention and affection due to the small number of orphanages, so children's education, especially Al-Qur'an and Arabic education, is often left behind compared to children of their age who live. in family. care. Therefore, programs related to the learning of the Qur'an and Arabic were made in order to have the capital of religious education. The method used is community-based research where the activities carried out are supported by the Lhokseumawe Muhammadiyah orphanage. According to the analysis, the activities carried out at the orphanage had a positive impact on the participants, some even being able to understand and speak Arabic. And their recitation of the Qur'an is better than before and their memorization of the Qur'an increases.